1994
DOI: 10.1037/0003-066x.49.1.42
|View full text |Cite
|
Sign up to set email alerts
|

On the AHCPR Depression in Primary Care guidelines: Further considerations for practitioners.

Abstract: The majority of cases of clinical depression go unrecognized and untreated, despite the fact that depression is an eminently treatable disorder. The Agency for Health Care Policy and Research (AHCPR) recently published a set of clinical practice guidelines focused on depression in primary care settings. The review of the literature on which the guidelines are based is thorough and appropriate and should enhance the detection of depression and the quality of pharmacotherapy for depression. However, the guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 134 publications
1
95
0
3
Order By: Relevance
“…Recent depression treatment guidelines [156, 157]do not seem to adequately reflect this tradition or the scientific evidence supporting these interventions. Current practice guidelines are considered by some [27, 130, 131, 132]to be inconsistent with the scientific literature in that they overstate the benefits of antidepressant medications and the combined treatment, understate the risks and side effects associated with pharmacotherapy, and understate the efficacy of psychotherapy. For example, the AHCPR summary guidelines [156]recommend two unsuccessful trials of antidepressant medication before even considering referral for psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent depression treatment guidelines [156, 157]do not seem to adequately reflect this tradition or the scientific evidence supporting these interventions. Current practice guidelines are considered by some [27, 130, 131, 132]to be inconsistent with the scientific literature in that they overstate the benefits of antidepressant medications and the combined treatment, understate the risks and side effects associated with pharmacotherapy, and understate the efficacy of psychotherapy. For example, the AHCPR summary guidelines [156]recommend two unsuccessful trials of antidepressant medication before even considering referral for psychotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Bearing in mind the limitations of meta-analyses [121, 122, 123], these studies, involving thousands of depressed patients, have found that (1) psychotherapy has an outcome that is comparable [124, 125]or better [126, 127]than that of pharmacotherapy alone, (2) combined psychotherapy and drug treatment do not appear to be clearly superior to either therapy alone [124, 125, 128], (3) when the dropout rate is considered, pharmacotherapy alone has a substantially worse outcome than psychotherapy alone or combined treatment [129]and (4) treatment with cognitive therapy (with or without drugs) during the acute episode appears to reduce the risk of subsequent relapse following termination [124]. Several reviews have concluded that the preponderance of the evidence does not support the differential effectiveness of psychotherapy and antidepressants in more severely depressed nonpsychotic outpatients [27, 130, 131, 132]. Actually most drug studies exclude some of the most severely depressed (e.g.…”
Section: Belief No 4: Antidepressants Are More Effective Than Psychomentioning
confidence: 99%
“…For example, most patients typically prefer psychological treatment over drugs in the treatment of depression, even though there is little empirical basis for choosing between them. If anything, the quality of the empirical support for the efficacy of pharmacotherapy is considerably greater than it is for the efficacy of psychological treatment ( Muñoz, Hollon, McGrath, Rehm, & VandenBos, 1994 ). Likelihood of compliance is also an important issue; many patients fail to benefit from treatments that might otherwise be effective because they are unable or unwilling to adhere to the treatment regimen.…”
Section: Treatment Feasibility Patient Acceptance and Compliancementioning
confidence: 99%
“…Considering that approximately half of the cases of depression are treated by general practitioners (Munoz, Hollon, McGrath, Rehm, & VandenBos, 1994), primary care seems a logical area for increased use of bibliotherapy.…”
Section: Self-administered Treatments For Depressionmentioning
confidence: 99%